International evidence-based recommendations for polycystic ovary syndrome in adolescents - Alexia S Peña; Selma Feldman Witchel; Jacky Boivin; Tania S. Burgert; Carolyn Ee; Kathleen M Hoeger; Marla E. Lujan; Aya Mousa; Sharon Oberfield; Chau Thien Tay; Helena Teede (BMC Medicine)
Abstract Background During adolescence, accurate diagnostic criteria and/or identification of adolescents “at risk” of polycystic ovary syndrome (PCOS) are critical to establish appropriate screening, treatment, and lifelong health plans. The 2023 International Evidence-Based Guideline for PCOS aimed to provide the most up-to-date evidence-based recommendations to improve health outcomes for individuals with PCOS, emphasizing accurate and timely diagnosis of PCOS from adolescence. Methods The best practice methods following the Appraisal of Guidelines for Research and Evaluation (AGREE-II) criteria were applied. Healthcare professionals and patients/consumers reviewed extensive evidence synthesis/meta-analysis for 55 prioritized clinical questions. Databases (OVID MEDLINE, All EBM, PsycInfo, EMBASE, CINAHL) were searched until August 2022 as part of the 2023 update of the Guideline. The Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) framework guided experts on evidence quality, feasibility, acceptability, cost, implementation, and ultimately recommendation strength. Results This manuscript focuses on the adolescent-specific recommendations of the 2023 Guideline. The diagnosis is based on the presence of both irregular menstrual cycles (defined according to the time postmenarche) and clinical/biochemical hyperandrogenism following the exclusion of other disorders that mimic PCOS. Adolescents with only one of these features can be considered “at risk” of PCOS requiring the management of symptoms and ongoing follow-up. Polycystic ovarian morphology on pelvic ultrasonography or anti-Müllerian hormone levels should not be used for diagnosis during adolescence. Lifelong health planning is recommended to include healthy lifestyles, screening for depression and metabolic features and the transition to adult care, all underpinned by shared decision-making. Healthcare professionals should explain weight-related health risks to adolescents, while minimizing weight stigma. In adolescents with PCOS or “at risk” of PCOS, combined oral contraceptive pills are indicated for menstrual irregularity and clinical hyperandrogenism, focusing on low dose preparations, and metformin could be considered for metabolic features and cycle regulation. Overall, the evidence is limited in adolescents with PCOS, and recommendations are based on low to moderate certainty evidence. Conclusions Extensive international engagement and rigorous processes generated International Guideline diagnostic criteria for adolescents that differ from adult criteria and clarified appropriate screening and management strategies for PCOS during adolescence.